Stabilizing small particles of lithium hydroxide with adsorbed water molecules: a quantum chemical study - Grebenyuk, A.G. (Поверхность, 2002)
Quantum chemical calculations have been carried out of the energetic and geometric characteristics of the lithium hydroxide molecular models within the frameworks of both semiempirical (the MNDO method) and ab initio (the STO-3G and 6-31G basises being used) approaches. The adsorption of water molecules has been shown to result in stabilizing small particles of the compound. The vibrational spectra of the LiOH microcrystallites have been also examined.